2007
DOI: 10.1113/jphysiol.2006.126573
|View full text |Cite
|
Sign up to set email alerts
|

The impact of murine strain and sex on postnatal development after maternal dietary restriction during pregnancy

Abstract: The objective of this study was to characterize offspring responses to maternal dietary restriction (DR) in two phylogenetically distant strains of mice: A/J and C57BL/6J (B6). Pregnant mice were fed 100% or 70% of ad libitum between 6.5 and 17.5 days (d) gestation. Offspring were fed 100% ad libitum postweaning. All comparisons were made to strain and sex matched controls. Male DR-B6 offspring initially grew slower than controls; however, by 77d and 182d they were significantly heavier (P < 0.05). Further, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…This is consistent with previous findings in rodent models, in which the weanling and adult offspring of HF diet-fed mothers exhibit increased adiposity, adipocyte hypertrophy, and increased hepatic and white adipose tissue expression of lipogenic and adipogenic genes (8,11,12,30,36,53,66). Previous studies have revealed sex differences in the developmental programming of obesity, insulin resistance, and hypertension, with males often being more sensitive to early-life programming events than females (22,38,60,68). In the present experiment, body composition was altered only in the male HF offspring from the first pregnancies; in subsequent pregnancies, this sexually dimorphic response was no longer observed.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous findings in rodent models, in which the weanling and adult offspring of HF diet-fed mothers exhibit increased adiposity, adipocyte hypertrophy, and increased hepatic and white adipose tissue expression of lipogenic and adipogenic genes (8,11,12,30,36,53,66). Previous studies have revealed sex differences in the developmental programming of obesity, insulin resistance, and hypertension, with males often being more sensitive to early-life programming events than females (22,38,60,68). In the present experiment, body composition was altered only in the male HF offspring from the first pregnancies; in subsequent pregnancies, this sexually dimorphic response was no longer observed.…”
Section: Discussionsupporting
confidence: 92%
“…Maternal calorie restriction in C57Bl/6J and A/J mice leads to reduced whole body BMC in B6 but not A/J offspring at 6 months of age [60], suggesting strain differences in sensitivity to maternal diet. Rats exposed to intrauterine growth restriction via uterine artery ligation are shorter, with narrower bones, lower whole body and femoral BMC, and lower bone strength in adulthood [6162].…”
Section: Maternal Body Composition Diet and Offspring Bone Massmentioning
confidence: 99%
“…Gene-by-environment interactions in sheep was evidenced in a study in which pregnant sheep from two breeds subjected to the same nutrient restriction resulted in offspring with different metabolic outcomes (Vonnahme et al, 2006). Similarly, studies in mice that tested gene-by-environment interactions found two strains of mice to have different metabolic outcomes to exposures during prenatal life (Knight et al, 2007). Because homogeneity of the genetic background of the Suffolk breed used in our studies was not controlled for, the genetic background is likely to differ within this breed between our earlier (Savabiesfahani et al, 2006) and this study; hence, this may account for the differences seen in preovulatory LH surge amplitude observed in the current study.…”
Section: Discussionmentioning
confidence: 99%